Development Potentials of Low Cost Aviation in the Republic of Croatia - Vidović, Andrija; Steiner, Sanja; Štimac, Igor (Promet - Traffic&Transportation, 2012)
The liberalization of the aviation market has enabled low-cost airlines to take over a significant share in the aviation market. Benefits of low-cost models are multiple, both for passengers and for secondary and regional airports, which were neglected in the past and which record significant inflow of passengers with the arrival of low-cost airlines. In the structure of the air traffic in the Republic of Croatia in the last ten years, there has been a progressive growth of foreign low-cost airline operations, which suggests a potential for the operation of a Croatian low-cost airline. This paper defines the criteria applicable to modelling of a low-cost airline in the Republic of Croatia in the relevant context of fleet management, route networking and operator’s processes in traffic technology. It analyzes the dynamics of low-cost airlines operations in the structure of air traffic in Croatia and the impact of traffic on the status of airports and the national operator. KEY WORDS: low-cost airline, traditional airline, airport, route network, fleet management